Fatores que interferem na sensibilidade do teste parasitológico no diagnóstico de leishmaniose visceral canina - Sousa, Marcus Vinícius Caetano de (2012)
This study aimed to investigate the sensitivity of parasitological testing when using aspirates or imprints of spleen, lymph nodes and bone marrow in function of time and correlate the parasite load of dogs with clinical symptoms. We used 31 seropositive dogs that were euthanized from the CCZ of Uberlândia. In the UFU s Laboratory of Pathology, the blades were fabricated and evaluated under a light microscope, 100X objective. The slides were evaluated for at most one hour and, if it was positive, the time spent for diagnosis in one, five, 20, 30 and 60 minutes were recorded. In the determination of the parasite load, the amastigotes were displayed and grouped in one, 10, 50, 100, and 500, 1000 and even 1500 views in 100 fields. Among the 31 animals analyzed, 11 (35.48%) were symptomatic, 17 (54.83%) oligosymptomatic and three (9.67%) asymptomatic. In the analysis by PAAF, difference was read of 20 minutes with one minute (p = 0.001), and the test sensitivity with time was greater at 60 minutes than at 20 minutes (p = 0.04). In the analysis of imprint, the test sensitivity was higher with time at 20 minutes than at five (p = 0.03). There was no statistical difference between the two techniques used in collecting samples for each tissue (bone marrow p = 1.0, p = 0.76 lymph nodes, spleen p = 0.57). There was no difference between tissues in the sensitivity of diagnoses made by PAAF, as well as imprint. The worm burden of both techniques demonstrated that asymptomatic animals have lower parasite load than in relation to symptomatic.